5‐Phenyl‐1, 3, 4‐oxadiazole‐2‐thiol/polyamide‐montmorillonite microbicides nanocomposites as drug delivery system. (22nd March 2018) - Salahuddin, Nehal; Elbarbary, Ahmed; Allam, Nanis G.; Hashim, Ayat F.
Abstract: The preparation and structural characterization of polymeric microbicides consisting of 5‐phenyl‐1, 3, 4‐oxadiazole‐2‐thiol covalently bound to polyamide based on diethyl‐2, 3‐dihydroxysuccinate and polyoxypropylenetriamine Jeffamine (T403 ) are described. Two different mole ratios of 5‐phenyl‐1, 3, 4‐oxadiazole‐2‐thiol was reacted with chloroacetylated diethyl‐2, 3‐dihydroxysuccinate followed by polycondensation with Jeffamine (T403 ). The nanocomposites were prepared by modification of microbicide polyamides to yield polymers with phosphonium salt or amine hydrochloride salt followed by ion exchange process between the phosphonium salt or amine hydrochloride of the polyamides and the intermellar sodium cation of the clay mineral montmorillonite. The monomers were characterized by mass spectrum, proton nuclear magnetic resonance. The polymers showed good or moderate antimicrobial activities. Nanocomposites were characterized by Fourier transformed infrared spectroscopy, X‐ray diffraction, thermal gravimetric analysis, and transmission electron microscope. The swelling behavior and release of 5‐phenyl‐1, 3, 4‐oxadiazole‐2‐thiol in different pH values (2.3, 5.8, and 7.4) were studied. A slow release, ranging from 12% to 28% after 50 hours was recorded from nanocomposites. However, the release profile reached almost 70% from polyamides. The antimicrobial activity of the polyamides was studied against gram‐negative bacteria, gram‐positive bacteria, yeast, and the filamentous fungi by well diffusion method. The polyamides showed better antimicrobial activities than 5‐phenyl‐1, 3, 4‐oxadiazole‐2‐thiol. Abstract : Polyamide‐loaded 1, 3, 4‐oxadiazoles intercalated into mineral montmorillonite (MMT) were prepared. The intercalation was achieved through an ion exchange process between sodium cations in MMT and phosphonium/ammonium groups attached to the polyamide‐loaded 1, 3, 4‐oxadiazoles. Higher loading of 1, 3, 4‐oxadiazoles in polymer shows lower release rates. The release profile from polyamide‐MMT nanocomposites in buffered aqueous solution under acid, neutral, and basic condition is indicative of a fairly strong dependence on the morphology of nanocomposites. The polyamides showed higher antimicrobial activities in comparison with 5‐phenyl‐ 1, 3, 4‐oxadiazole‐2‐thiol.